(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In today’s rapidly changing world, the key characteristics of the quality of the organization of the educational process in the classroom in accordance with the requirements of state educational standards of higher education are the use of modern educational technologies and electronic educational resources. qualification of pedagogical workers in the part relating to the methodology of designing a modern training session, which is impossible without author’s methodological developments and electronic educational resourcesin.